Rejuvenating American Politics - Leathe, Becca (Maine Policy Review, 2004)
To promote Senator Margaret Chase Smith’s firm belief in the importance of civic engagement, on the eve of the 2004 presidential elections the Margaret Chase Smith Library invited Maine high school seniors to submit essays proposing ways to encourage young people to become more involved in the political process. We feature here Becca Leathe’s first place prize-winning essay, which draws upon historical examples as well as personal experiences and opinions.